The dark tower, and other stories - Lewis, C. S. (Clive Staples), 1898-1963.; Hooper, Walter (New York : Harcourt Brace Jovanovick, 1977)
"The Dark Tower is incomplete, but a vivid and highly interesting tale of the use of an imaginary device - a Chronoscope - that lets you view an other time the way you would view a star with a telescope. Lewis himself is in the story as one of a group of friends/scholars who meet to watch the happenings of the Dark Tower in the 'Othertime.' The story is intense and riveting and I couldn't put it down, but there are pages missing in the middle of the manuscript supposedly discovered after Lewis's death as a newly discovered, previously unpublished work. The end of the short story is also absent ... and there is no indication of how close to the end the reader is to the ending when the story is cut off literally in mid sentence. The positive thing is that the story is so well written, it will keep your mind reeling as to the outcome and fate of the characters involved. I've heard that the claims that this is an actual true work of C.S. Lewis is now being disputed, but if it is not of his hand, it sure reads like his style.'The Man Born Blind' is an interesting account of a man born blind who gets his sight as an older adult and struggles with visual concepts such as 'what is light.' It's a very short story and if any of the stories in this volume are to be disputed, this one would be my pick ... it doesn't read like Lewis and I think Lewis was far more observant of human nature and of his environment in general to have made some of the assumptions he did in this very short story.' The Shoddy Lands' is pure Lewis ... almost like 'The Great Divorce, ' but in miniature. Very interesting explaination at the end that wasn't exactly what I was reading into it at first ... a very good story.' Ministering Angels' is not at all what you think it's about ... but nonetheless an interesting futuristic tale of life on a human-colonized Mars. Also a very short story, but it's amazing how Lewis can depict a character so richly and vividly in just a few lines"--Amazon.com.
Hooper, W. Preface. -- The dark tower, with a note by W. Hooper. -- The man born blind. -- The shoddy lands. -- Ministering angels. -- Forms of things unknown. -- After ten years, with notes by R.L. Green and A. Fowler.
Keywords: Manners and customs -- Fiction; Manners and customs; Fiction